2014
DOI: 10.1037/a0035887
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of life satisfaction five years after medical discharge for traumatically acquired disability.

Abstract: Results suggest that being married and greater family satisfaction promote life satisfaction among those who traumatically acquire disability, and these beneficial effects may be more salient than the degree of functional impairment imposed by the condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
0
18
1
Order By: Relevance
“…Several authors found that people suffering from lifetime trauma (Krause 2004 ; Triplett et al 2012 ), having PTSD symptoms (Besser and Neria 2009 ; Karatzias et al 2013 ), suffering from a traumatically acquired disability (Hernandez et al 2014 ) or perceiving severe stress (Kaya et al 2015 ) generally experience less satisfaction with life. Only a few studies refer to the relationship between religious fundamentalism and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors found that people suffering from lifetime trauma (Krause 2004 ; Triplett et al 2012 ), having PTSD symptoms (Besser and Neria 2009 ; Karatzias et al 2013 ), suffering from a traumatically acquired disability (Hernandez et al 2014 ) or perceiving severe stress (Kaya et al 2015 ) generally experience less satisfaction with life. Only a few studies refer to the relationship between religious fundamentalism and life satisfaction.…”
Section: Introductionmentioning
confidence: 99%
“…Findings indicated that being married and having greater family satisfaction were associated with trajectories of higher life satisfaction over the first 5 years following injury. 14 Another longitudinal study found that marital loss had a consistent negative impact on the SWB of SCI participants, but the effects were moderated by gender. 15 Because SWB and needs change over time, outcomes at a single time point provide a limited view and do not reflect the dynamic changes.…”
mentioning
confidence: 99%
“…15 Because SWB and needs change over time, outcomes at a single time point provide a limited view and do not reflect the dynamic changes. With few exceptions, 14,15 most studies on this topic are cross-sectional and cannot address the long-term impact of marital status after SCI. Our purpose was to examine 20-year longitudinal data to identify the relationship between marital status and trajectories in SWB over time after SCI.…”
mentioning
confidence: 99%
“…It contains 5-items with response options on a 7-point Likert scale (1 = strongly disagree to 7 = strongly agree) that are added for a summary score [ranging from , with higher scores indicating greater SWL. For this study, SWL was dichotomized as: low SWL (≤20) and average/high SWL (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35), as described by Diener. 22 Our rationale for dichotomizing the SWL scores was to provide an easily understandable interpretation of a global measure based on individual's judgments of ideal standards.…”
Section: Methodsmentioning
confidence: 99%
“…The dependent variable, SWL, was examined descriptively. Bivariate analyses to assess differences in demographics, injury characteristics, chronic conditions, symptoms, social support, grief/loss, and independence in individuals who reported low SWL (≤20) vs. average/high SWL (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) were conducted. A multivariate logistic regression model was used to assess factors independently associated with low SWL [reference: average/high SWL].…”
Section: Analysesmentioning
confidence: 99%